2020
DOI: 10.1016/j.freeradbiomed.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Plasma pharmacokinetics of (poly)phenol metabolites and catabolites after ingestion of orange juice by endurance trained men

Abstract: A. (2020) Plasma pharmacokinetics of (poly)phenol metabolites and catabolites after ingestion of orange juice by endurance trained men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…Previous studies suggested that the regular intake of orange juice (OJ) reduces inflammatory reactions and oxidative stress. OJ flavanones, mainly naringenin-7-rutinoside and hesperetin-7-O-rutinoside, are reported to have a wide range of beneficial attributes on human health such as the improvement of lipid profile [37,38]. Garlic belongs to the Allium genus and is traditionally used as a medicinal plant all over the world.…”
Section: Plant-derived Bioactive Componentsmentioning
confidence: 99%
“…Previous studies suggested that the regular intake of orange juice (OJ) reduces inflammatory reactions and oxidative stress. OJ flavanones, mainly naringenin-7-rutinoside and hesperetin-7-O-rutinoside, are reported to have a wide range of beneficial attributes on human health such as the improvement of lipid profile [37,38]. Garlic belongs to the Allium genus and is traditionally used as a medicinal plant all over the world.…”
Section: Plant-derived Bioactive Componentsmentioning
confidence: 99%
“…Feliciano et al, 2017;R. P. Feliciano, A. Boeres, et al, 2016;Henning et al, 2013;Keane et al, 2015;Koli et al, 2010;Lang et al, 2013;Li et al, 2000;Loke et al, 2009;Ludwig et al, 2015;McKay et al, 2015;Mueller et al, 2017;Ottaviani et al, 2016;Pereira-Caro et al, 2020;Pimpão et al, 2015;Prymont-Przyminska et al, 2016Rodriguez-Mateos et al, 2016Rodriguez-Mateos, Rendeiro, et al, 2013;Russell et al, 2009;Sandhu et al, 2018;Scherbl et al, 2016;Stalmach et al, 2012Stalmach et al, , 2009Stalmach et al, , 2014Suárez et al, 2009;Urpi-Sarda et al, 2009;van der Pijl et al, 2015;van Duynhoven et al, 2014;Vitaglione et al, 2007;Zhang & Zuo, 2004;Zhong et al, 2017).…”
Section: Intervention Studies Identifying and Quantifying The Lmw Phe...unclassified
“…We have searched PubMed for human intervention studies, which have identified and quantified LMW phenolic metabolites in human blood using diets rich in (poly)phenols or using flavonoid supplementation. In total, we have identified 42 intervention studies that employed either (i) dietary sources such as fruits or derivates thereof (e.g., juice, fruits, cake, coffee) in a single dose (Supplementary Table 2), (ii) dietary sources in multiple doses (Supplementary Table 3), or (iii) supplementation using plant extracts or pure flavonoids in capsules (Supplementary Table 4) (Azzini et al., 2010; Bresciani et al., 2017; Caccetta et al., 2000; Castello et al., 2018; Curtis et al., 2019; Czank et al., 2013; Rachel M. de Ferrars, Czank et al., 2014; R. M. de Ferrars, Cassidy et al., 2014; de la Torre et al., 2003; R. Feliciano et al., 2017; R. Feliciano, Istas, et al., 2016; R. P. Feliciano, A. Boeres, et al., 2016; Henning et al., 2013; Keane et al., 2015; Koli et al., 2010; Lang et al., 2013; Li et al., 2000; Loke et al., 2009; Ludwig et al., 2015; McKay et al., 2015; Mueller et al., 2017; Ottaviani et al., 2016; Pereira‐Caro et al., 2020; Pimpão et al., 2015; Prymont‐Przyminska et al., 2016, 2014; Rodriguez‐Mateos et al., 2016, 2014; Rodriguez‐Mateos, Rendeiro, et al., 2013; Russell et al., 2009; Sandhu et al., 2018; Scherbl et al., 2016; Stalmach et al., 2012, 2009, 2014; Suárez et al., 2009; Urpi‐Sarda et al., 2009; van der Pijl et al., 2015; van Duynhoven et al., 2014; Vitaglione et al., 2007; Zhang & Zuo, 2004; Zhong et al., 2017).…”
Section: Intervention Studies Identifying and Quantifying The Lmw Phe...mentioning
confidence: 99%
“…Chlorogenic acids PII/MM Plasma/urine [32,33] Phenolic acids [34] PI [35] PII Plasma [36] MM [37] Green tea Flavan-3-ols PII Urine [38] PII/MM [39] Black tea Hydroxybenzoic acids [40] Flavonoids and phenolic acids Plasma/urine [41] Yerba mate Flavonols and phenolic acids [42] Orange juice Flavonoids and phenolic acids PII Plasma/urine [43] Flavanones and flavonols Urine [44] Flavanoids PII/MM [45] Flavanones [46] Plasma/urine [47] Red wine…”
Section: Coffeementioning
confidence: 99%